Case Study on Cycloconverter with PI Voltage Control for Single Phase Induction Motor - Mohd Nazri, Syafiqah Shahirah; Zulkifli, Shamsul Aizam (Evolution in Electrical and Electronic Engineering, 2021)
This paper is to highlight several case studies in order to simulate a single phase cycloconverter for induction motor voltage control using MATLAB/Simulink, with a Proportional Integral (PI) control technique. The cycloconverter comprises of back-to-back connected controlled thyristor, where its output voltage and frequency can be controlled by tuning the PI gains in order to give reference firing angles to be adjusted to switching cycle for thyristor voltage control. An AC voltage of 24V with a fundamental frequency of 50Hz source is applied for the motor operation. The simulation results show that, the output voltage feedback at the motor is changed accordingly to the reference voltage, set at the controller input where the PI controller can provide a required voltage for the induction motor. At the end it helps the authors to understand the concept of voltage control at power converter topologies.